Role of ultrasonic examination in assessment of the knee-joint state in patients with juvenile idiopathic arthritis - V. O. Roschina; V. D. Zavadovskaya; N. G. Zaviyalova; A. N. Kailina; Yu. P. Chasovskikh (Бюллетень сибирской медицины, 2012)
uvenile idiopathic arthritis (JIA) belongs to a heterogeneous group of chronic inflammatory joint diseases in children, which begin under 16, tend to progressive joint disease involving synovium with chondrolysis, destruction of bone structures, and often formation of ankylosis.To reveal structural changes in knee joints, 25 children with JIA were passed through ultrasonic examination with the use of 7.5—11 (14) MHz linear sensors in superscale mode with energy and color Doppler mapping. Standard laboratory indices, rheumatoid factor (RF), and modified citrullinated vimentin antibodies (MCVA) in blood serum by the ELISA method were determined as well. The JIA activity was assessed using the DAS28 index. In the examination of knee joints in the group with JIA, most characteristic changes were uniform synovium thickening (68% of cases) with proliferation and vascularization (in 50% at proliferation), joint capsule effusion (56% cases) with mean values of (4.16 ± 2.47) mm. Reliable correlation has been revealed between synovium vascularization and MCVA level, erythrocyte sedimentation rate, and DAS28 activity, as well as thickness of joint effusion with MCVA level.